Teledentistry to prevent periodontal disease in geriatric patients during the COVID-19 pandemic - Falcón-Guerrero, Britto Elbert (2021)
When patients reach an advanced age, they usually present a higher prevalence of periodontal diseases, so the dental treatment they receive will be a fundamental factor in maintaining their oral health (1,2).